2012
DOI: 10.1103/physrevlett.108.157402
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Laser Emission of ZnO Nanowires Explained by Many-Body Theory

Abstract: Are excitons involved in lasing in ZnO nanowires or not? Our recently developed and experimentally tested quantum many-body theory sheds new light on this question. We measured the laser thresholds and Fabry-Pérot laser modes for three radically different excitation schemes. The thresholds, photon energies, and mode spacings can all be explained by our theory, without invoking enhanced light-matter interaction, as is needed in an earlier excitonic model. Our conclusion is that lasing in ZnO nanowires at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…From the calculations, the carrier density, where the gain overcomes the losses in the bulk ZnO, was estimated to be n g ∼ 2.1 × 10 25 m 3 . This value is clearly larger than the Mott density (n Mott ∼ 1.5 × 10 24 m 3 ), 14 which is one of the criteria for distinguishing excited electronic states between excitonic and EHP states. The threshold carrier density n th (in m 3 ) was estimated from the excitation intensity and the following differential equation:…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…From the calculations, the carrier density, where the gain overcomes the losses in the bulk ZnO, was estimated to be n g ∼ 2.1 × 10 25 m 3 . This value is clearly larger than the Mott density (n Mott ∼ 1.5 × 10 24 m 3 ), 14 which is one of the criteria for distinguishing excited electronic states between excitonic and EHP states. The threshold carrier density n th (in m 3 ) was estimated from the excitation intensity and the following differential equation:…”
Section: Figmentioning
confidence: 92%
“…So far, as gain materials, many studies on UV ZnO lasers have also been reported in various micro-/nano-cavity structures, such as random structures, [1][2][3][4][5][6][7][8][9][10][11][12][13] Fabry-Perot cavities, [14][15][16][17] whispering-gallery-mode resonators. [18][19][20][21] Although, in most of these ZnO lasers, the gain from electron-hole plasma (EHP) recombination under high excitation intensity condition has typically been reported as the origin of the stimulated emission (photon lasing), 12,13 the lasing originated by excitonic recombination, so-called polariton/exciton lasers, has also been demonstrated in well-designed cavity structures at room temperature.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Any significant effect of the shape of the absorption profile can therefore be ruled out. Since laser oscillations are likely caused by the formation of an electron-hole plasma (EHP) at high pumping intensities in single CdS (and ZnO NWs as a comparable NW laser system) [14,16,27,17], the approximately 1.24 times higher absorption for parallel polarization supplies the semiconductor more efficiently with charge carriers. This is further accompanied by a red-shift of the gain profile at the same pumping powers due to band gap renormalization effects in the EHP [28].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, every resonance corresponds to a bound state and we find that the last resonance occurs at the Mott-density n M 2.3 × 10 24 m −3 . Densities up to two orders of magnitude above the Mott density are readily obtainable below the damage threshold of ZnO, in bulk as well as nanowire samples [27,31]. For carrier densities that are larger than the Mott density, the scattering length always remains negative.…”
Section: -4mentioning
confidence: 99%